SISTEM PAKAR UNTUK MENGANALISA PENYAKIT TANAMAN PADI BERDASARKAN GEJALA MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Hilda Dwi Yunita; Rio Idha (Jurnal TAM (Technology Acceptance Model), 2019)
Many cases of rice farmers have difficulty coping with various types of diseases due to lack of knowledge and rarely counseling about the types and characteristics of rice diseases and how to overcome them. and the disease can cause losses to rice farmers. To overcome the above problems, the need to build a system that acts as a tool for rice farmers to analyze diseases that attack rice plants. The system in question is an expert system. The method used is Forward Chaining. From the results of the study, this system of rice disease experts was able to analyze the disease of rice plants based on their symptoms as a substitute tool for an expert. But for the results of the diagnosis can not provide solutions or suggestions that are really appropriate in handling it.